Hieracia balcanica XV. Taxonomic and nomenclatural notes on Hieracium pilosissimum and H. divaricatum, with remarks on the H. heldreichii aggregate (Asteraceae) - Szeląg, Zbigniew (Phytotaxa, 2018)
The original material of Hieracium pilosissimum Friv. nom. illeg. is heterogeneous and includes the type of H. divaricatum. Contrary to previous opinions, Hieracium pilosissimum is found conspecific with H. olympicum, whereas H. divaricatum may have originated as the result of hybridization between H. petrovae and H. racemosum. Earlier confusion caused the misuse of the name H. sect. Pilosissima for hybridogenous taxa between principal species of H. sect. Pannosa and species belonging to other sections. Hieracium pilosissimum is lectotypified using a specimen held at W. Hieracium cappadocicum var. congestum is synonymised with H. cappadocicum. Hieracium olympicum var. jankae is synonymised with H. olympicum and lectotypified. Hieracium rumelicum is synonymised with H. divaricatum and lectotypified. Hieracium thessalum, as morphologically intermediate between H. pannosum s. lat. and H. sparsum, is excluded from the H. heldreichii aggregate and lectotypified.